A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages Staff Personnel It is generally recognised that one of the principal difficulties to be overcome in order to ensure an adequate flow of suitable entrants into the nursing profession is to bridge the gap between the age when the average girl leaves school and the age when training can be commenced. Some girls are virtually “born nurses” and others quite easily acquire a knowledge and a keen interest in the profession, given the opportunity. Arrangements should be made whereby any girl with a good standard of education and the necessary enthusiasm should be regarded as a potential qualified nurse. Tradition dies hard. The school of thought that holds steadfastly to the opinion that a girl should be at least 18 years of age before she embarks upon a new life as a probationer is, it is felt, mistaken. N.A.L.G.O. holds a higher opinion of the young woman of to-day. She is physically and mentally several years ahead of the pre-war girl and is quite capable of meeting all reasonable demands upon her energies at an age earlier than 18 years. The recruitment of nursing staff demands complete reconsideration. It is futile to let the system remain static and expect the material to find ways and means of adjustment. The system must be made to conform to modern requirements if for no other reason than that comparatively few parents can afford to continue their girls’ education up to 18 years of age. N.A.L.G.O. Proposals on Recruitment, Training and Qualifications Given the necessary support of the nursing profession in the employ of local authorities, N.A.L.G.O. will take every possible step towards implementing the following policy :— 1. Local Authorities and the Board of Education to be urged to establish suitable courses of instruction in anatomy, physiology and hygiene ; also, if practicable, courses in food values, cooking and household management :— (a) as an optional part of the curriculum for girls in secondary schools up to age 17-18 ; (b) as an extension of the curriculum of technical schools providing two years’ training from age 15-16 ; (c) in evening continuation schools open to all from age 15 upwards ; (d) under Student Nursing Schemes. Entrants (subject to a form of agreement with the parents) to be regarded as eligible for suitable scholarships or maintenance grants throughout the course. 5 292/54.73/2/1